(untitled) (Fiep Bulletin - online, 2011)
The present study is an evaluation on the proficiency of the number of converted balls of foul shots and it relationship between the fundamental motor patterns of it of ten females players of the team which represents the municipality o Santarém in Pará State at the age of 18 to 25 years old. The sample was made by a census group, in which was examined the possible relationship between the motor patterns that makes part of fundamental motor pattern of the motor gesture of free shots and the proficiency of the shot knew by the numbers of converted balls of each player. The tests that have been used were the evaluation protocol of the fundamental motor pattern of foul shot that were developed by Marcus Hodwar (2006) showed an interaction between the proficiency of the foul shot in each player with the entire motor pattern that compounds the fundamental motor pattern in basketball free shots.